Dystrophia myotonica with hypercapnic respiratory failure – local challenges and ethical dilemmas / Muhammad Amin Ibrahim ... [et al.] - Ibrahim, Muhammad Amin; Raja Zulkifly, Raja Noor Azimah; Tan, Hui-Xin; Azman Ali, Raymond (Faculty of Medicine, 2025)
Dystrophia myotonica type 1 (DM1) is an adult-onset progressive form of muscular dystrophy which eventually lead to respiratory f ailure. Non-invasive home mechanical ventilation (HMV) f or these patients could result in a reduced risk of morbidity and mortality. The f ollowing case report describes the management of respiratory f ailure in a patient with DM, and the challenges that come with it especially in our Malaysian settings.